APLIKASI TAZKIYATUN NAFS DALAM PSIKOTERAPI ISLAM - Zakia, Arini Zakia; Maryatul kibtiyah; Hilma Nadia Faylasufa; Abdullah Nur; Ahmad Zidni Ilman (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2024)
This research also focuses on how to describe the concept of tazkiyah an-nafs as a method of purifying the soul in Islam with a focus on its main principles and stages. The method used in this research is Library Research or (Library Study), namely data collection by reading existing literature either using books, notes, or research results from previous studies that have something to do with the article to be discussed. Tazkiyatun nafs is a central concept in Islam that refers to the process of purifying the soul and heart from all moral impurities, such as despicable traits and sins. This process aims to achieve moral and spiritual perfection and get closer to Allah SWT. The main goal of tazkiyatun nafs is to form individuals who have noble character, faith, and piety. By cleansing the heart of liver disease, individuals can be more open to receiving knowledge and wisdom. Tazkiyah al-nafs is also the key to achieving inner peace and true happiness. Through various methods, namely (1) cleaning the soul from despicable traits (takhalli) (2) adorning the soul with praiseworthy traits (tahalli) and (3) revealing the veil to Allah SWT because the condition of the soul is pure (tajall).